Peran Sanggar Batik dalam Mempertahankan Warisan dan Identitas Budaya Melayu serta Ekonomi Kreatif: Studi Kasus di Jambi Seberang - Ica Puspitasari; Lisa Puspitasari; Mafrohatul Lutfiah; Dewi Miftahul Khasanah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Jambi Batik is one of the cultural heritages of the Malay community that possesses significant historical, philosophical, and economic values, making its preservation essential amid the challenges of globalization and modernization. Batik studios serve as strategic institutions for sustaining the tradition of batik making while supporting the development of the local creative economy. This study aimed to analyze the role of batik studios in preserving Malay cultural heritage and identity, as well as their contribution to the development of the creative economy in Jambi Seberang. The research employed a literature review method with a descriptive qualitative approach. Data were collected from various secondary sources, including books, scientific journal articles, previous research, government documents, and other relevant references related to batik, Malay culture, cultural preservation, and the creative economy. Data were analyzed using content analysis through the processes of identifying, classifying, interpreting, and synthesizing relevant information. The findings indicate that batik studios function as centers for cultural preservation by transmitting batik-making skills, preserving distinctive Jambi batik motifs, introducing Malay cultural values, and fostering younger generations' appreciation of local culture. Furthermore, batik studios contribute to the creative economy by generating employment opportunities, empowering local communities, supporting micro-enterprises, encouraging product innovation, promoting cultural marketing, and developing batik-based educational tourism. However, these studios continue to face several challenges, including the limited regeneration of batik artisans, competition from mass-produced batik-patterned products, limited financial resources, inadequate human resource capacity, and suboptimal utilization of digital technology. Therefore, sustainable collaboration among the government, local communities, academics, and business stakeholders is essential to strengthen cultural preservation while enhancing the competitiveness of the batik-based creative economy in Jambi Seberang.